Gonadotropin-releasing hormone analog therapies for children with central precocious puberty in the United States - Jadranka Popovic; Mitchell E. Geffner; Alan D. Rogol; Lawrence A. Silverman; Paul B. Kaplowitz; Nelly Mauras; Philip Zeitler; Erica A. Eugster; Karen O. Klein (Frontiers Media S.A., 2022)
Gonadotropin-releasing hormone agonists (GnRHa's) are the standard treatment for children with central precocious puberty (CPP). We aim to present data on available GnRHa options with an easy-to-review table and discuss factors that influence treatment selection. Five GnRHa's are currently FDA-approved and prescribed in the US and published data suggest similar safety and efficacy profiles over the first year of treatment. One- and 3-month intramuscular (IM) leuprolide acetate (LA) have long-term safety and efficacy data and allow for flexible dosing. Six-month IM triptorelin pamoate offers a longer duration of treatment, but without long-term efficacy and outcome data. Six-month subcutaneous (SQ) LA combines a SQ route of injection and long duration of action but lacks long-term efficacy and outcome data. The 12-month SQ histrelin acetate implant avoids injections and offers the longest duration of action, but requires a minor surgical procedure with local or general anesthesia. Factors in treatment selection include route of administration, needle size, injection volume, duration of action, and cost. The current GnRHa landscape provides options with varying benefits and risks, allowing physicians and caregivers to select the most appropriate therapy based on the specific needs and concerns of the child and the caregiver. Agents have different advantages and disadvantages for use, with no one agent displaying superiority.